Diammonium Glycyrrhizinate Mitigates Liver Injury Via Inhibiting Proliferation Of NKT Cells And Promoting Proliferation Of Tregs - Gao M; Li X; He L; Yang J; Ye X; Xiao F; Wei H (Dove Medical Press, 2019)
Meixin Gao,1,* Xiulan Li,2,* Lingling He,3 Junru Yang,3 Xiaohui Ye,3 Fan Xiao,4 Hongshan Wei1–3 1Department of Gastroenterology, Peking University Ditan Teaching Hospital, Beijing 100015, People’s Republic of China; 2Center of Liver Diseases, Beijing Ditan Hospital, Capital Medical University, Beijing 100015, People’s Republic of China; 3Department of Gastroenterology, Beijing Ditan Hospital, Capital Medical University, Beijing 100015, People’s Republic of China; 4Institute of Infectious Diseases, Beijing Ditan Hospital, Capital Medical University, Beijing 100015, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hongshan WeiDepartment of Gastroenterology, Beijing Ditan Hospital, Capital Medical University, No. 8, Jingshun East Street, Chaoyang District, Beijing 100015, People’s Republic of ChinaEmail drwei@ccmu.edu.cnPurpose: Diammonium glycyrrhizinate (DG) is a replacement for glycyrrhizic acid, which is used as a hepatic protector in clinical practice for most liver diseases. The potential role of immune response during autoimmune hepatitis—induced by concanavalin A (Con A)—remains to be elucidated.Methods: C57BL/6J mice were treated with two different doses of DG (75 and 200 mg/kg) 2 hrs before administering Con A. The mice were sacrificed after administering Con A for 0, 6, and 24 hrs. Liver damage grade and serum alanine aminotransferase (ALT), aspartate aminotransferase (AST) and total bilirubin levels were evaluated. The expression level of cleaved-caspase 3 in liver was detected by Western blotting. Inflammatory cytokines such as tumor necrosis factor α (TNF-α), interleukin-6 (IL-6), and interferon γ (IFN-γ) in liver were detected by RT-PCR. Thymus, peripheral blood, spleen, and liver tissues were collected to analyze the percentages of NKT cells, subsets of CD4+CD25−CD69+ and CD8+CD69+ T cells, and subsets of regulatory T cells (Tregs).Results: Our results revealed that DG pre-treatment significantly decreased the serum ALT and AST levels and improved the histological damage in Con A-induced autoimmune liver injury. Pre-treatment with DG down-regulated the inflammatory cytokines upon challenge with Con A. The DG pre-treatment inhibited the apoptosis of T lymphocytes in the thymus. Further, it effectively suppressed the proliferation of CD4+CD25−CD69+ and CD8+CD69+ subsets in the peripheral blood and spleen. In addition, the DG pretreatment significantly downregulated the frequency of NKT cells, while upregulating the frequency of Tregs in the liver.Conclusion: We believe that the potential protective effect of DG against Con A-induced hepatitis may be partially attributed to its inhibitory activities on inflammatory cytokines in the livers, lymphocyte apoptosis in the thymus, NKT cells proliferation, and activation of CD8+T cells; further, there may also be a possibility of DC promoting Tregs proliferation.Keywords: autoimmune hepatitis, concanavalin A, diammonium glycyrrhizinate, NKT cells, regulatory T-cell